Subcritical water hydrolysis of N-acetyl-D-glucosamine: hydrolysis mechanism, reaction pathways and optimization for selective production of 5-HMF and levulinic acid - Kulkarni, Sphurti Prakash; Dure, Shital N.; Joshi, Sunil S.; V. Pandare, Kiran; Mali, Nilesh A. (Carbohydrate Research, 2022)
In this study, the subcritical water hydrolysis of N-acetyl-D-glucosamine (NAG), a monomer of abundant renewable marine biopolymer chitin, for production of value-added chemicals is investigated. The enhanced ionization of water at subcritical conditions (200 degrees C; 50-100 bar), provides enough acidity for deacetylation of NAG resulting in 80% yield of acetic acid along with traces of formic acid, lactic acid, glucose, fructose, 5hydroxymethylfurfural (5-HMF),etc. The significant humin formation indicates that the self-condensation and polymerisation of 5-HMF is favored in water at subcritical conditions. A catalyst p-toluenesulfonic acid (p-TsOH) was employed to selectively convert NAG to levulinic acid (LA) via ring opening of 5-HMF previously formed during hydrolysis. The maximum yield of 27.13 +/- 1% and 53.46 +/- 1% of 5-HMF and LA, respectively, was obtained at process conditions optimized using Box-Behnken design coupled with response surface methodology. Subcritical water enables greener conversion of NAG to platform chemicals wherein the selective production can be achieved by tuning the process conditions.
Keywords: 5-Hydroxymethylfurfural; chitin; Glucosamine; levulinic acid; Response surface methodology; Subcritical water